(3GdWQjbI GdeMeOjI hGdSjQI GdCMeOjIs - (3eMeO Hf HjQ Ydj Hf EScfOQ GdHQcdj GdQhej , eMjj GdOjf, J (B981 (3g` s ((3eMeO Hf eMehO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYdfG CeI hSWG hHYO aEf GdYbd hGdfbd eJhGabGf hGdcJGH hGdSfI eJWGHbGf s
(3BNQgG (B:s
(3hWGdYgG MJi JYde MbjbI ebGdfG hfbhd GdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi Je HYhf Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HChdg hbajI HGSe GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi GdHjQhJis
(3eDQNI SfI (B1373(3g`s
(3HgG fXGe GdJYbjHI s
(3HChdgG agQSJ ddCHhGH s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs